The transition to the service society: prospects for growth, productivity and employment - Henning Klodt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The paper explores the basic features of structural change towards services for OECD countries in general and for Germany in particular. The determinants of sectoral shifts are analytically decomposed into the demandbias and the productivity-bias. The demand-bias, which prevails in all OECD countries, mainly reflects the spread of service-based new technologies and related shifts in intermediate demand. The productivity-bias is valid for most countries, but not for Germany, where service sector expansion concentrated on highly productive disembodied services. This anomaly in structural change restricted the capacity of the German service sector to absorb dismissed industrial workers.
Keywords: L80; O50; J21; 330; Drei-Sektoren-Hypothese; Strukturwandel; Dienstleistungssektor; Produktivität; Gesamtwirtschaftliche Nachfrage; Unternehmensdienstleistung; Beschäftigungseffekt; Strukturelle Arbeitslosigkeit; Deutschland